A Razão Áurea e suas aplicações - Santos, Carlos Gonçalves dos (2010)
When we talk about Mathematic, we think in numbers, rarely the student has in his domain evidence to think about Mathematic as ideas. The numbers have bad fame. The Mathematics’ classes had been remembered of traumatic form to students. The main idea of this research is to show that Mathematics is a subject that goes beyond the classroom, and over the centuries, was a great aid to all sciences, and presented it presence in different areas of knowledge. We’ll use the Aurea Reason, also known like Proportion Divine or Golden Number, considered until today as a great Geometry treasure. The Aurea Reason represents the most pleasant proportion between two segments or two measures, and we can found it in simple matters of everyday thus facilitating their comprehension. We’ve carried a historical study and we’ve presented the history of some greats Mathematical that have contributed to Aurea Reason like various applications in different knowledge areas and its presence in the human body. This research considers the introduction of methodologies to develop student’s capacity for abstraction, allowing a clear connection between symbolic languages, used in textbooks, and concepts involved in the relation’s discovery, they are essential to the learning of Math become more than a tool for solving everyday problems, been a pleasure for the student